2005
DOI: 10.1177/089686080502500309
|View full text |Cite
|
Sign up to set email alerts
|

The Time Course of Serum C-Reactive Protein is More Predictive of Mortality than its Baseline Level in Peritoneal Dialysis Patients

Abstract: Background Several recent studies reported that a high baseline serum C-reactive protein (CRP) is a powerful predictor of mortality in dialysis patients. However, the acute-phase response is intermittent and not a continuous feature in an individual patient. The aim of this prospective study was to determine whether serial analysis of serum CRP during follow-up allows better prediction of mortality and echocardiographic cardiac disease than a single baseline measurement in peritoneal dialysis (PD) patients. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…On the one hand, the impaired host defence due to the long-term exposure of the conventional glucose dialysate and malnutrition [ 26 – 29 ] may be the main contributor to the poor outcomes in long-term PD patients when exposed to an episode of peritonitis, although this notion needs to be clarified. On the other hand, a longer duration of PD may also be associated with chronic inflammation [ 30 32 ] and cardiovascular calcification [ 33 , 34 ], which are risk factors for overall and CV mortality in PD patients. In addition, ESRD patients on dialysis for a number of years were associated with higher levels of alkaline phosphatase [ 35 , 36 ], which is traditionally a marker of high-turnover bone disease in ESRD patients but was recently found to be an independent predictor of adverse outcomes of peritonitis in PD patients [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, the impaired host defence due to the long-term exposure of the conventional glucose dialysate and malnutrition [ 26 – 29 ] may be the main contributor to the poor outcomes in long-term PD patients when exposed to an episode of peritonitis, although this notion needs to be clarified. On the other hand, a longer duration of PD may also be associated with chronic inflammation [ 30 32 ] and cardiovascular calcification [ 33 , 34 ], which are risk factors for overall and CV mortality in PD patients. In addition, ESRD patients on dialysis for a number of years were associated with higher levels of alkaline phosphatase [ 35 , 36 ], which is traditionally a marker of high-turnover bone disease in ESRD patients but was recently found to be an independent predictor of adverse outcomes of peritonitis in PD patients [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…A similar finding was also reported by Ateş et al, showing variation in CRP levels during regular follow-up. 29 In the present study, the result of the multivariable Cox regression mode analysis revealed that the time-average serum HS-CRP level, instead of the baseline HS-CRP level, was an independent predictor of mortality and dropout in patients on PD. The ROC curve analysis also demonstrated that the mortality predictability of serum time-averaged HS-CRP level was superior to that of the serum baseline HS-CRP level.…”
Section: Discussionmentioning
confidence: 46%
“…This study demonstrated that 164 patients on PD (49.0%) had elevated time-averaged serum HS-CRP levels (>5 mg/L), similar to the Turkish report (47.4%). 29 In this study, patients in the high time-averaged serum HS-CRP tertile had a higher mortality and dropout rate during the 60-month follow-up. Correspondingly, the multivariate Cox regression analysis also demonstrated that the time-averaged serum HS-CRP level is superior to a single baseline measurement as an independent predictor of mortality and dropout.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Additionally, biological inter-individual and intra-individual variability of CRP levels in dialysis patients might be greater than the variability in health individuals [ 1 ]. Nevertheless, only a few small studies have assessed the consequences of longitudinal conventional CRP, but not hs-CRP, fluctuation on mortality among peritoneal dialysis (PD) patients [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%